Het humanitaire optreden van Leopold II in Kongo-Vrijstaat. De Anti-Slavernijconferentie van Brussel (1889-1890) - Chatelet, Luc (Afrika Focus, 1988)
Already from the time he was a crown prince Leopold II dreamt of acquiring a colony. He firmly believed in the economic importance for the motherland of overseas territories. However, when he appeared on the African scene he presented himself as a champion of the struggle against slave trade. This disinterested humanitarian image was meant as a means of bypassing Belgian indifference towards colonization and also the foreign rivalry. But in Africa he was forced into an opportunist policy. A total lack of means left him no other choice but resorting to political and economic collaboration with the Arabs, who played a major role in the slave trade. It was at the moment when the European colonization met the Arabic resistance in East-Africa that Cardinal Lavigerie's campaign called for renewed public interest in the struggle against the Arabic slave trade. Great Britain asked Belgium to summon a diplomatic conference on the subject. In 1889 seventeen nations gathered to discuss a whole range of measures to limit slave trade on land and sea, arms trade and liquor traffic. The hottest issue on the agenda was the imposition of import duties in the Congo bassin. The main obstacle to the introduction of these taxes was the Dutch opposition against the changing of the terms of the Berlin Act (1885). The General Brussels Act did not include import tax regulations. These were the subject of a separate declaration, which Leopold however managed to connect to the General Act in such a way that neither could be ratified singly. Hence, the customs committee, convened after the Brussels negotiations to define more clearly the import duties, was an essential factor in the Antislavery Conference. It was not until 1892 that all obstacles were overcome and the final discussions rounded off. The Brussels Antislavery Conference did not induce Leopold to come to grips with slave trade and did not alter his Arabic policy. For the sovereign the conference was primarily a matter of economy and taxes. He wanted his colony to have more promising financial prospects. His attitude was conditioned by the precarious budget of the Congo Free State. The conference fitted in his new economic policy which consisted in carrying out his domanial projects. KEYWORDS: colonial history, colonization and humanitarianism, Leopold II, Antislavery Conference of Brussels (1889- 90), economic policy